RIAS Learning Model: a Character Education Innovation - Ahmad Muhlisin; Sri Sarwanti; Gentur Jalunggono; Arnanda Yusliwidaka; Sukron Mazid; Achmad Busrotun Nufus (AL-ISHLAH: Jurnal Pendidikan, 2021)
Character education has not been well facilitated in every learning process; hence, several indications of low character among college students are found. This research aims to develop a new learning model based on character education to enhance students’ spiritual and social attitudes. The research was a research and development by adopting Borg Gall’s research and development procedures. The research procedures consist of the following steps: 1) Library study, 2) designing a model design, 3) learning model development, 4) expert validation, and 5) focus group discussion with users and students. Instruments used in the research include content validity and construct validity sheets of the learning model with an assessment scale score of 1-5 that ranges from (1) not feasible, (2) less feasible, (3) fairly feasible, (4) feasible, and (5) very feasible. The research results indicate that 1) character-based learning innovation resulted in RIAS learning model with main steps of Reading, Identification, Analysis, and Self-reflection, 2) RIAS learning model has a validation score of 4.6 within a valid category; thus, it is feasible to be utilized to enhance social and spiritual attitudes. The suggested for further research is testing the effectiveness of the RIAS learning model on a wide scale and testing the effect of the RIAS learning model on problem-solving and student learning outcomes.